Efficient P, O chelate palladium(II)/AgNO3 cocatalyzed homocoupling of aromatic terminal alkynes in aqueous media under ambient atmosphere. (4th March 2017) - Chen, Bo; Guo, Mengping; Wen, Yongju; Shen, Xiuli; Zhou, Xiuling; Lv, Meiyun
GRAPHICAL ABSTRACT: ABSTRACT: A new and efficient protocol for the P, O chelate Pd(II)/AgNO3 cocatalyzed oxidative homocoupling reaction of aromatic terminal alkynes in the synthesis of symmetrical 1, 4-disubstituted-1, 3-diynes was described in aqueous media under ambient atmosphere. The results showed that both NEt3 and THF/H2 O (in 4:1 proportion) played crucial roles in the reaction. In contrast, this protocol employs a low palladium(II) complex loading and AgNO3 as cocatalyst to obtain the homocoupled products in moderate to good yields.